Research trends on early contractor involvement in construction projects: A bibliometric analysis - Osuizugbo, Innocent Chigozie; Muhammad Ashraf, Fauzi; Omer, Mazen M.; Njogo, Bibiana O.; Orekan, Atinuke Adebimpe (Australian Institute of Quantity Surveyors, 2024)
The present study aims to highlight most significant journals in early contractor involvement (ECI) research, most productive authors on ECI studies and territories, geospatial network of the active ECI research countries, current trend in ECI studies, and the most relevant keywords and co-occurrence networks in ECI studies. This study comprehensively examined the ECI research field by conducting a bibliometric analysis of 210 journal articles between 1992 and 2023 from the Web of Science (WoS) database. The findings showed that, Transportation Research Record, Construction Management and Economics, Journal of Management in Engineering, and Journal of Construction Engineering and Management are the most represented journals. Per Erik Eriksson from Luleå University of Technology is the most productive author identified in this study. United States of America, England and Australia are the most productive countries on ECI research. Current trends in ECI studies include ECI and project delivery, ECI as critical success factors, ECI in design and its impact on construction schedule performance and overcoming cost-related issues through ECI. The highest co-occurred keywords are “procurement”, “early contractor involvement”, “performance,” and “construction.” The findings from this study suggest that applying Collaborative contracting theory to ECI enhances innovation, project delivery, and communication, while relational contracting theory fosters collaborative risk management, trust, and flexibility, resulting in better relationships and outcomes. To the best of the authors’ knowledge, this study is the first to conduct bibliometric analysis of past studies on ECI. As a result, the study contributed to the existing knowledge by identifying the pattern and trend of ECI research area, revealing its broader themes of research and clusters, mapping the network of key ECI authors and territories. This study identified “governance structure” as an aspect of ECI study that is scarce in the literature and needs further exploration. Additionally, since most ECI studies originate from developed countries, future research should focus on developing countries.